A High Rate of Return to Running Is Seen After Both Arthroscopic and Open Shoulder Surgery - Joseph W. Galvin, D.O.; John M. Slevin, P.A.-C.; Matthew J. Nowak, D.O.; Henry H. Yu, M.D.; Eric K. Turner, M.D.; Brian R. Waterman, M.D.; Jason A. Grassbaugh, M.D.; Edward D. Arrington, M.D. (Arthroscopy, Sports Medicine, and Rehabilitation, 2023)
Purpose: To determine the percentage of patients who report the ability to run 1 mile at various time points after arthroscopic and open shoulder surgery. Methods: We performed a retrospective review of prospectively collected data for all active-duty military patients aged 18 to 45 years who underwent shoulder surgery at a single institution over a 2-year period. The rehabilitation protocol discouraged running before 3 months, but all patients were able to return to unrestricted running at 3 months postoperatively. Patients were excluded if they lacked 1-year follow-up data. Parameters collected included demographic information and validated patient-reported outcome measures at the preoperative and short-term postoperative visits, as well as patients’ ability to run at least 1 mile postoperatively. Results: A total of 126 patients were identified who underwent shoulder surgery with return-to-running data. Compared with baseline, significant improvements in patient-reported outcomes were shown at 1 and 2 years postoperatively (P = .001). The percentage of patients reporting the ability to run 1 mile postoperatively was 59% at 3 months, 74% at 4.5 months, 79% at 6 months, 83% at 12 months, and 91% at 24 months. There was no significant difference in patients undergoing shoulder surgery for instability versus non-instability diagnoses or in patients undergoing open versus arthroscopic anterior stabilization. All 11 patients unable to return to running at final follow-up had chronic lower-extremity diagnoses limiting their running ability. Conclusions: Young military athletes undergoing arthroscopic and open shoulder surgery have a high rate of early return to running. Approximately 60% of patients report the ability to run 1 mile at 3 months postoperatively, and three-quarters of patients do so at 4.5 months. Age, sex, military occupation, underlying diagnosis or type of surgery did not influence the rate of return to running after shoulder surgery. Level of Evidence: Level IV, therapeutic case series.